STRATEGI PENGUATAN POSISI TAWAR PETANI BAWANG DAUN MELALUI PENGUATAN KELEMBAGAAN - Ana Arifatus Sa’diyah; Dyanasari Dyanasari (Universitas Tribhuwana Tunggadewi, 2016)
The purpose of this research are to determine : (1) the marketing channel that efficient scallion cultivation ; (2) institutional in scallion cultivation and its role in the marketing of scallion cultivaion ; (3) To know the scallion farmers' bargaining position ; (4) determine institutional strengthening strategy and its relationship with the scallion growers bargaining scallion farmers . The analytical method used in this research is descriptive method of analysis . The research results show : there are 4 chain marketing channels of scallion in Probolinggo district , and VI channel is the most efficient channel ; There are two agricultural institutions in the location of research , namely cooperatives and farmer groups that have a role on the marketing of scallion ; Bargaining position of farmers in the location of research is still relatively low ; and Institutional Strengthening Strategy farmers in order to improve the bargaining position of farmers one of them can be done with intensive training on institutional members